The Effects of Issue Characteristics on the Recognition of Moral Issues - Chia, Andrey (Journal of business ethics, 2000)
The construct of moral intensity, proposed by Jones (1991), was used to predict the extent to which individuals were able to recognize moral issues. We tested for the effects of the six dimensions of moral intensity: social consensus, proximity, concentration of effect, probability of effect, temporal immediacy and magnitude of consequences. A scenario-based study, conducted among business individuals in Singapore, revealed that social consensus and magnitude of consequences influenced the recognition of moral issues. The study provided evidence for the effects of temporal immediacy. There was marginal support for the impact of proximity and probability of effect but no evidence that concentration of effect influenced recognition of moral issues. The paper concludes with a discussion of the implications of these results for researchers and organisational practitioners.